Ischemic heart disease in children and young adults with congenital heart disease in Sweden. (1st December 2017) - Fedchenko, Maria; Mandalenakis, Zacharias; Rosengren, Annika; Lappas, Georg; Eriksson, Peter; Skoglund, Kristofer; Dellborg, Mikael
Abstract: Background: An increasing proportion of congenital heart disease (CoHD) patients survive to an age associated with increased risk of developing ischemic heart disease (IHD). The aim was to investigate the risk of developing IHD among children and young adults with CoHD. Methods: Using the Swedish National Patient Register, we created a cohort of all CoHD patients born between January 1970 and December 1993. Ten controls matched for age, sex, county were randomly selected from the general population for each patient (n = 219, 816). Patients and controls were followed from birth until first IHD event, death, or December 31, 2011. Results: We identified 21, 982 patients with CoHD (51.6% men), mean follow-up was 26.4 (21.2–33.9) years. CoHD patients had 16.5 times higher risk of being hospitalized with or dying from IHD compared to controls (95% CI: 13.7–19.9), p < 0.0001. Patients with conotruncal defects and severe nonconotruncal defects, had the highest IHD incidence rate (71.1 and 56.3 cases per 100, 000 person-years, respectively, compared to 2.9 and 2.3 in controls). Hypertension and diabetes were less common among CoHD patients with IHD than among controls with IHD (hypertension 9.7% vs 19.7%, diabetes 1.8% vs 7.7% in CoHD patients and controls). Patients with aortic coarctation did not have a specific increase in the risk of developing IHD or acute myocardial infarction. Conclusions: In this large case-control cohort study, the relative risk of developing IHD was markedly higher in CoHD patients than in controls. However, the absolute risk was low in both groups.